2014
DOI: 10.2478/pjvs-2014-0090
|View full text |Cite
|
Sign up to set email alerts
|

Methyl paraben as a sex pheromone in canine urine – is the question still open?

Abstract: The literature concerning the issue of canine sex pheromones includes reports presenting completely conflicting opinions about the chemical composition of the canine urine in the context of semiochemical communication. At present, the predominant report cited by many different authors is the article published in Science in 1979 by Goodwin at al., presenting methyl p-hydroxybenzoate (methyl paraben) as the main canine sex pheromone. While it has been proved that pure methyl paraben lacks semiochemical activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…EtP and PrP were found in dog urine at mean concentrations of 1.0 and 0.5 ng/mL, respectively, which were 2 orders of magnitude lower than MeP concentrations. MeP has been reported as a sex pheromone in canines, and some commercially available male sexual stimulants in the United States (as recommended by veterinarians and dog breeders) contain MeP. , The mean concentration of total parent parabens in dog urine was 130 ng/mL, which was 2- to 11-fold higher than those reported for human urine from the U.S. population. , Among the metabolites, 4-HB was found highest, at a mean concentration of 5150 ng/mL, which was 7 to 8 times higher than those reported for human urine from the U.S. population . It is noteworthy that 4-HB has been used as a food preservative and corrosion inhibitor and as an additive in drugs, cosmetics, and dyes.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…EtP and PrP were found in dog urine at mean concentrations of 1.0 and 0.5 ng/mL, respectively, which were 2 orders of magnitude lower than MeP concentrations. MeP has been reported as a sex pheromone in canines, and some commercially available male sexual stimulants in the United States (as recommended by veterinarians and dog breeders) contain MeP. , The mean concentration of total parent parabens in dog urine was 130 ng/mL, which was 2- to 11-fold higher than those reported for human urine from the U.S. population. , Among the metabolites, 4-HB was found highest, at a mean concentration of 5150 ng/mL, which was 7 to 8 times higher than those reported for human urine from the U.S. population . It is noteworthy that 4-HB has been used as a food preservative and corrosion inhibitor and as an additive in drugs, cosmetics, and dyes.…”
Section: Resultsmentioning
confidence: 86%
“…Parabens are esters of p -hydroxy benzoic acid and are broad-spectrum antimicrobial agents used in personal care products, pharmaceuticals, and food products. Both in vitro and in vivo studies have demonstrated that parabens are endocrine-disrupting chemicals (Darbre and Harvey, 2008) . Exposure to parabens was linked to reproductive effects in men. , The U.S. FDA and the European Food Safety Authority (EFSA) have set the permissible limits for parabens in human food products. , Exposure of humans to parabens, however, is ubiquitous. Nevertheless, little is known on the exposure of pet animals to parabens and their derivatives . We determined the concentrations of parabens and their metabolites in cat and dog urine as well as pet food available commercially for these companion animals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could not be the explanation for the case described here, firstly because no products containing these compounds had been used on the case dog, and because other studies have excluded the pheromonal effect of methylparaben in dogs [ 18 , 59 , 60 ]. Finally, despite the hypothesis of Goodwinn et al [ 8 ], the presence of this compound has been excluded from the group of compounds present in the urine of the bitch in estrus [ 15 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…In domestic dogs, mechanisms of attracting males by a female in estrus were studied and attempts to identify the substance(s) responsible for this phenomenon were undertaken [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. In most research, urine was considered a main source of attractants, although effective artificial sex pheromones have not yet been definitively identified [ 20 ].…”
Section: Introductionmentioning
confidence: 99%